Natural and crop management-related conditions for spring feed barley production - Bartosiewicz, Beata; Poręba, Ludwika (Polish Journal of Agronomy, 2019)
Barley is a cereal of great economic importance, dominatingin the cropping patterns of spring cereals. Currently, springforms are grown primarily for fodder purposes. The correct selectionand preparation of a stand for cultivation and the correcttiming of crop management practices (sowing, disease managementand fertilization adapted to the habitat conditions), as wellas the selection of high-yielding and disease-resistant varieties,are vital to secure high crop yields with good quality parameters.Lack of knowledge of the interaction between habitat and cropmanagement factors negatively affects the quantity and qualityof barley crop.